Delirium in elderly individuals with hip fracture: causes, incidence, prevalence, and risk factors - Maria Elizabet Furlaneto; Luiz Eugênio Garcez-Leme (Clinics, 2006)
OBJECTIVES: To determine the incidence, prevalence, risk factors, and causes of delirium in elderly individuals with hip fractures, as well as the impact of delrium on mortality and length of hospital stay. PATIENTS: One hundred and three patients aged 65 and older with hip fractures were included consecutively between January 2001 and June 2002. METHOD: Delirium was diagnosed using the Confusion Assessment Method, applied within the first 24 hours after admission, and then daily. All patients underwent a global geriatric evaluation including clinical history, physical examination, laboratory tests, surgical risk evaluation, and functional and mental evaluations. Patients with delirium (cases) were compared with patients without delirium (controls). RESULTS: Thirty (29.1%) patients in this sample met the criteria for delirium, with a prevalence of 16.5% (17/103) and an incidence of 12.6% (13/103). Cognitive and functional deficits had a significant association with delirium, although only cognitive deficit was revealed to be an independent risk factor after analysis with the logistic regression model. The most frequent causes of delirium were drugs and infections. The hospital stay was significantly longer for patients with delirium compared with patients in the control group (26.27 versus 14.38 days, respectively). Mortality showed a tendency to higher levels in patients with delirium during their hospital stay, although with no statistical significance. CONCLUSIONS: Delirium is a frequent complication among hospitalized elderly individuals with hip fractures. It is associated with cognitive and functional deficits, and it is associated with increases the length of hospital stay and mortality.